On the Theme of Immortality Through Literature in Shakespeare’s Sonnets - Min Peng (Randwick International of Education and Linguistics Science Journal, 2020)
William Shakespeare’s 154 Sonnets contribute a great deal to art and literature. As a world-class master, he lives in the English Renaissance period, which is marked by a cultural flowering. Humanism is the essence of the Renaissance. It dramatically affects Shakespeare’s works. In the sonnets, he reinforces his affirmation of human wisdom and knowledge of creating magnificent literature, thus bringing about the immortality of youth and beauty, which is an acute reflection of his humanistic thought of the Renaissance. This paper takes the humanism of the Renaissance as its concept. Then, this paper concentrates on investigating the theme of immortality through literature in these sonnets, including Sonnet 15, 17, 18, 19, 55, 60, and 81. After interpreting the themes with concrete examples, this paper summarizes that Shakespeare’s yearning for immortality through literature derives from his humanistic spirit. Additionally, this paper is of higher significance for valuing the principle of putting people first at the core, while pursuing a comprehensive, balanced, and sustainable development in modern society.